Hepatitis B Virus Genotype-Dependent Vulnerability of Infected Cells to Immune Reaction in the Early Phase of Infection - Shiina, Masaaki; Yamada, Norie; Sugiyama, Ryuichi; Murayama, Asako; Aly, Hussein Hassan; Muramatsu, Masamichi; Wakita, Takaji; Imawari, Michio; Kato, Takanobu (Frontiers in Microbiology, 2019)
Infection with hepatitis B virus (HBV) genotype (GT)-A has been reported to predispose patients to chronic infection. To explore genotype-dependent pathogenicity, a system mimicking the immune reaction during the early phase of HBV infection is important. To this end, we established a coculture system with HBV molecular clone-transfected HepG2 cells and immortalized human natural killer (NK) cells. After coculture with NK cells, we found that GT-A-positive HepG2 cells exhibited lower susceptibility to NK cell-induced cell death than GT-B- or GT-C-positive HepG2 cells. NK cell-induced degranulation and cytokine production were not different among HepG2 cells transfected with different HBV genotypes. The expression levels of death receptors in HBV-transfected HepG2 cells were not different. In GT-A-positive cells, a similar low susceptibility was detected by the administration of tumor necrosis factor (TNF), although relatively higher susceptibility was observed in GT-B- and GT-C-positive cells than in GT-A-positive cells. The activation of caspase signaling was revealed to be responsible for this genotype dependency. In conclusion, our results indicate that the HBV genotype does not influence the NK cell function itself but rather cell vulnerability through the TNF signal pathway. This observation may explain the high chronicity rate of HBV GT-A strains even in adult infections.